If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+5=2(6x+5)
We move all terms to the left:
7x+5-(2(6x+5))=0
We calculate terms in parentheses: -(2(6x+5)), so:We get rid of parentheses
2(6x+5)
We multiply parentheses
12x+10
Back to the equation:
-(12x+10)
7x-12x-10+5=0
We add all the numbers together, and all the variables
-5x-5=0
We move all terms containing x to the left, all other terms to the right
-5x=5
x=5/-5
x=-1
| -3/4(15x-30)=198 | | -7-2y=-3-3y | | 6x=27/13 | | 9j=29 | | 4x–1=2x+11 | | -19+2z=21 | | 5x+3=7-9 | | X+2x=3x+24 | | (5x-12)^3=12 | | ⅈ=3/100x12 | | 6y+46,5/10=7,35 | | (5x-12)^=12 | | x/3=x-10=4 | | 0.45m=0.9m | | x/3=x-10= | | 5y–2=28 | | 5x+-23=17 | | X=470+-8.4x | | 40=120x | | 2x+8=‐3x+17 | | 21x-1=11x | | x-4=x/3+1/3 | | 10x2=9x+7 | | 9y-3=36y+3 | | 4m-m=75+15 | | 300-x=300-x | | 5x-11=+3x | | 20=9*x-2 | | m+5=8(m+16) | | 13+x=4x+5 | | 7/8=x/96 | | 5(x–3)=3(x+7) |